A comprehensive modeling on MoS2 interface and defect engineering in CZTS thin film solar cells - Islam M.S.; Doroody C.; Kiong T.S.; abar F.I.Z.; Bin Bahrudin M.S.; Rahman K.S.; Boon Kar Y.; Zuhdi A.W.M. (Elsevier Editora Ltda, 2025)
This work -incorporates the SCAPS-1D modeling program toexamine the impacts of defects in the Molybdenum Disulfide (MoS2) layer and the MoS2 interface on the electrical performance of CZTS solar cells. To get an ideal energy gap (Eg) of 1.3 eV and a carrier concentration (CC) of 1014 cm??, the research attempts to optimize the CZTS absorber layer. By maintaining a consistent doping level with 1016 cm-3 CC and an Eg within 1.6 eV < Eg 1.8 eV for the MoS2 film, the work also investigates the possibility of increased efficiency in CZTS/MoS2 devices. The study results indicate that open circuit voltage (VOC) and Efficiency (Eta-?) parameters are improved by a p-type MoS2 interface, indicating a promising development for CZTS solar cells. Nonetheless, n-type MoS2 suggests a compromise with a reduction in the fill factor. The study emphasizes the stability benefits of a p-type MoS2 interface as well as the importance of surface recombination velocity. The study also considers phase transitions that occur during the device manufacturing, highlighting the intrinsic n-type character of MoS2 and the importance of experimental methods in CZTS device optimization. After analyzing the effects of defects on carrier density, depletion width, and quantum efficiency, the study concludes that enhancing the performance of CZTS solar cells requires an acceptor-type interface with p-type MoS2. With recombination resistances of 443.92 cm2, 1530.33 cm2, 81.54 cm2, and 93.82 cm2, the SCAPS model shows zero series resistance at a particular site for the fundamental, optimized design using n-MoS2 and p-MoS2. In the end, the work sheds light on the possibilities for additional experimental studies to advance the technology of CZTS solar cells. ? 2024 The Authors